THE EFFECT OF NON PERFORMING FINANCING, OPERATIONAL EFFICIENCY RATIO, AND SIZE FIRM ON PROFITABILITY OF ISLAMIC BANKING IN INDONESIA - Sari, Annisa Fitri Anugrah; Fauzi, Achmad; Respati, Dwi Kismayanti (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
This research aims to determine the effect of Non Performing Financing (NPF), Operational Efficiency Ratio (BOPO), and Size Firm on Profitability of Islamic Banking in Indonesia. The data collection method used is the study documentation method. This research will collect data on the annual financial report on The Financial Services Authority (OJK) website. The affordable collection in this study was Islamic Rural Banks (BPRS) listed on The Financial Services Authority (OJK) in 2018 – 2020 with 144 banks. The sample used were as many as 102 banks using random sampling and Isaac and Michael function. The data analysis techniques used are multiple linear regression, pre-requirement test, classic assumption, and hypothesis analysis. The research shows that NPF has a significant negative effect on profitability, BOPO has a significant negative impact on profitability, and size firm has a negative, not significant effect on profitability. The coefficient of determination in this study was 22,8% which showed the ability of NPF, BOPO, and size firms to influence profitability. In contrast, the rest were influenced by other factors that were not examined.